Mineralogical Evaluation of Au-Sb-As Mineralization from the ADMW Zones, Clarence Stream Property, New Brunswick - Louis J. Cabri; Donald Hoy (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
"Samples with contrasting gold mineralization were studied quantitatively prior to metallurgical tests. The AD samples are coarser-grained and characterized by abundant Sb minerals (jamesonite, berthierite, stibnite). The finer-grained MW sample has abundant pyrite and pyrrhotite, with arsenopyrite and galena next in abundance. A large number of gold mineral particles were determined by SEM investigation of hydroseparation concentrates, ranging from 150 to 597 per sample. The grain-size distribution of the gold minerals shows evidence of bimodal grain-size distributions (volume %), with the coarse fraction being most significant in sample MW-1 (maximum ECD=308µm). The coarsest gold minerals in the AD samples range from 139µm to 281µm ECD.The deportment of gold minerals is as electrum, aurostibite, native gold, and a possible new mineral (AuNiSb4). Gold also occurs in nisbite. The gold minerals are dominated by electrum in three samples and aurostibite is next in abundance. The major gold minerals are probably representative of three stages of gold mineralization. The first stage is represented by electrum, which is partly to completely replaced by Sb-rich mineralization forming aurostibite, and the last stage is native gold, often occurring as rims on one or the other earlier gold mineral. The gold minerals are strongly associated with sulphides in the AD samples (55 to 60 vol.%). At the grind used for the hydroseparation the liberated gold mineral quantity (volume %) is also significant, ranging from 65% for sample MW-1 to 30 to 37% for the AD samples.INTRODUCTIONThe Clarence Stream deposit is located 70 km south-southwest of Fredericton and 25 km northnorthwest of St. George, south-western New Brunswick, near the international boundary with Maine (Fig. 1)."